Valuation of Environmental Impact Due to Material Construction Mining, Gowa, South Sulawesi - Andi Arjan; Arikah Nurhusna Afifah; Yubelium Andrew Patila; Aryanti Virtanti Anas (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2020)
Sand, river stone, soil excavation, sandstone and broken stone are the types of construction materials mining in Gowa Regency and many are found in the Jeneberang River. The Jeneberang River is one of the main rivers in South Sulawesi. However, construction materials mining carried out around the Jeneberang River has a negative impact on the surrounding environment. Those negative impacts are erosion, road damage, noise, air pollution, and decrease in water quality. This research was conducted in Gowa Regency. The method used is the Contingent valuation method (CVM). CVM consists of the desire to pay (Willingness to Pay or WTP) and the desire to accept (Willingnes to Accept or WTA. While the social aspect conducts interviews with questionnaire questions to respondents to find out opinions about the surrounding environment. From this study, it is known that WTP and WTA data are inversely proportional. The greater the compensation to be paid, the more societies who want to receive and the fewer companies paid for the compensation.